The Quail Response of Growth Period to Protein Level and Synthetic Methionine Addition in Ration - Roesdiyanto, Roesdiyanto; Suhermiyati, Sri; Suswoyo, Imam (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 1999)
A researchÂ has been conducted to study the effect of interaction between protein level and synthetic methionine addition in quail ration on growth rate up to 40 days. The method was used experiment with Factorial (3x3) based on CRD. The first factor was protein level (P) : P1 = 22 %, P2 = 24 %, P3 = 26 %. The second factor was methionine addition (M) : M0 = 0,00, M1 = 0,05 %, M2 = 0,10 %. Variance analysis indicated that protein level did not have significant effect (P>0.05) on feed consumption, growth rate, feed conversion, weight and percentage of carcass, but it had significant effect (Pâ¤0.05) on IOFC. The effect of methionine addition was not significant (P> 0.05). Interaction between those treatments did not give significant effect (P>0.05). It can be concluded that the response on 26 % protein level with 0,05 % methionine addition give the highest IOFC (Rp. 342.693) (Animal Production 1(1) : 17-23 (1999).Â Key Words : Quail, Growing Periode, Protein Level, Synthetis Methionine.